Perfil de expressão de microRNAs circulantes em carcinomas de fígado, pâncreas e vias biliares - Bertoni, Natália [UNESP] (2017)
Background: Hepatic-pancreatic-biliary tract (HPB) cancers are aggressive carcinomas with common progenitor cells, suggesting that molecular mechanisms of tumorigenesis can be shared between these tumors. MicroRNAs (miRNAs) are important gene expression regulators and have been identified as biomarkers with clinical application in the diagnosis, prognosis and treatment of patients with cancer. The aim of this study was to identify the expression profile of plasma miRNAs in patients with HPB carcinomas and potential biological processes involved in the carcinogenesis of these tumors. Patients and Methods: Twelve plasma samples were analyzed, 4 of which were obtained from patients with hepatocellular carcinoma, 4 with pancreatic adenocarcinoma and 4 with cholangiocarcinoma, and 10 plasma samples from healthy individuals (reference group). The expression profile of circulating miRNAs was determined using the TaqMan Array Human MicroRNA Cards (card A, v3.0) platform. Prediction analysis of target mRNAs potentially regulated by the identified miRNAs and target miRNAs-mRNAs interaction networks were performed. Results: Among the 42 differentially expressed miRNAs identified in plasma obtained from patients with cancers of the liver, pancreas and biliary ducts, 28 miRNAs (67%) were shared between the three tumor subtypes, being 19 under-expressed and 9 over-expressed. MiRNA target predictions followed by enrichment analysis revealed putative target genes associated with transcription, cell division, organization, differentiation, proliferation and apoptosis. Among the under-expressed miRs are: miRs let-7b-5p and let-7c-5p, predicted to regulate genes associated with cancer, HMGA2 and ZNF516; and miR-660-5p, miR-25-3p and miR-92a-3p, which regulate the HAS3 gene. Interestingly, miRNAs with increased expression (mir-130b-3p, miR-142-5p, miR-148a-3p, miR-152-3p, miR-130a-3p and miR-27b-3p) were predicted to regulate genes involved in cellular development. Among them, miR-142-5p showed the highest number of target genes (19 genes). Conclusion: The identification of miRNAs commonly dysregulated in plasma from patients with HPB carcinomas and not in healthy controls suggests an association of these alterations with tumorigenesis mechanisms of these carcinomas. In addition, target genes predicted to be regulated by these miRNAs encode important proteins with different cellular processes with an important role in tumorigenesis. Validation studies in a large number of cases may contribute to the development of new diagnostic and therapeutic strategies for patients with HPB carcinomas.